Post-Digital Cultures of the Far Right Online Actions and Offline Consequences in Europe and the US - Fielitz, Maik; Thurston, Nick (transcript-Verlag, 2018)
How does the far right operate today? This volume presents a unique critical survey of the online and offline tactics, symbols and platforms that are strategically remixed to stake national and transnational cultural claims by contemporary far-right groups in Europe and North America. Featuring short, accessible analyses by an international range of expert scholars, policy advisors and activists, the book offers a plurality of answers to practical and theoretical questions about how and why the Internet has been crucial to emboldening extreme nationalisms in these regions and what counter-cultural approaches civil societies should develop in response
Keywords: Culture; Digital Media; Europe; European Politics; Far Right; Internet; Media Studies; Media; Political Science; Politics; Right-wing Extremism; Extrémistes de droite; Fascisme; Médias numériques; Nationalisme blanc; Digital media; Fascism & Nazism; fascism; Fascism; Political Science / Political Ideologies / Fascism & Totalitarianism; Right-wing extremists; White nationalism; Digital media -- Political aspects; Internet -- Political aspects; Rechtsradikalismus; Netzwerk; Social Media; Symbol; Subkultur; Europa; USA; Electronic books; Essay; Essais; essays; Essays; Aufsatzsammlung